A heterometallic [LnLn′Ln] lanthanide complex as a qubit with embedded quantum error correction. Issue 38 (9th September 2020) - Macaluso, Emilio; Rubín, Marcos; Aguilà, David; Chiesa, Alessandro; Barrios, Leoní A.; Martínez, Jesús I.; Alonso, Pablo J.; Roubeau, Olivier; Luis, Fernando; Aromí, Guillem; Carretta, Stefano
Abstract : We show that a [Er–Ce–Er] molecular trinuclear coordination compound is a promising platform to implement the three-qubit quantum error correction code protecting against pure dephasing, the most important error in magnetic molecules. Abstract : We show that a [Er–Ce–Er] molecular trinuclear coordination compound is a promising platform to implement the three-qubit quantum error correction code protecting against pure dephasing, the most important error in magnetic molecules. We characterize it by preparing the [Lu–Ce–Lu] and [Er–La–Er] analogues, which contain only one of the two types of qubit, and by combining magnetometry, low-temperature specific heat and electron paramagnetic resonance measurements on both the elementary constituents and the trimer. Using the resulting parameters, we demonstrate by numerical simulations that the proposed molecular device can efficiently suppress pure dephasing of the spin qubits.